E-ORDER PADA PERCETAKAN BERBASIS WEB - Atik Budi Paryanti; Wahyu Dwi Rangga (STIKOM CKI, 2019)
Rapid technological development makes people work more efficiently, including the transaction process. Percetakan Rezeki Bersaudara is a company that runs in the printing sector, which does a lot of transactions every day. However, in the transaction process, Percetakan Rezeki Bersaudara still uses a manual system so that it does not have a system that is efficient in material and time aspects. The creation of a new computerized system is expected to improve efficiency in both material and time aspects. Data collection methods that I use qualitative types, namely by means of observation and interviews. From this study produced a web-based transaction system application. This application increases the level of efficiency in the material aspect because it does not require paper in the process, and also improvesefficiency in the aspect of time because it uses a computer network so that transactions can be done faster.